A Children’s Asthma Education Program: Roaring Adventures of Puff (RAP), Improves Quality of Life - Shawna L McGhan; Eric Wong; Heather M Sharpe; Patrick A Hessel; Puish Mandhane; Vicki L Boechler; Carina Majaesic; A Dean Befus (Canadian Respiratory Journal)
BACKGROUND: It is postulated that children with asthma who receive an interactive, comprehensive education program would improve their quality of life, asthma management and asthma control compared with children receiving usual care.